Analisis Strategi Komunikasi Untuk BerkAnalysis of Communication Strategies for Sustainability in Forming and Maintaining Organizational Cultural Values at the STIAMI Institute elanjutan Dalam Membentuk dan Mempertahankan Nilai - Nilai Budaya Organisasi Di Institut STIAMI - Danang Aji Pangestu; Firdaus Suwarta; Tri Indahsari; Wulan Furrie (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research explores communication strategies in forming and maintaining organizational culture at the STIAMI Institute. In the midst of the dynamics of globalization, educational institutions, such as the STIAMI Institute, are faced with the challenge of maintaining a culture that supports the educational vision. The research uses a qualitative approach with in-depth interviews as a data collection method. The research findings reflect the positive steps the STIAMI Institute has taken, while highlighting areas of potential improvement. The consistency of message interpretation, the impact of communication media, the implementation of ethical values, the culture of innovation, and the responses of organizational members are the focus of analysis. Recommendations involve in-depth evaluation, measuring the impact of digital media, and further analysis of the implementation of ethical values. This research provides insight into communication strategies that support the establishment of a sustainable organizational culture in educational environments, contributing to a better understanding of the complexity of cultural dynamics at the STIAMI Institute